The development of a customized data logger for quality control in brewing - Pelser, Petrus Cornelis (Bloemfontein: Central University of Technology, Free State, 1997)
The P.U. (Pasteurization Unit) recorder is an instrument used to measure the temperature variation and conditions dwing the pasteurization of packaged beer. It is effectively a data logging instrument used for quality control in the beverage brewing industry. The P. U. recorder is unique in the sense that it has to do measurements and complicated calculations in very harsh humid temperature conditions while providing a PC intetface in order to download data to the factOIY MIS (Management Infonnation System). The project is aimed at developing a new improved and customized instlUment that could replace an imported product used in the SA brewing industly. Furthermore, this product has the potential to penetrate intemational markets. Although the development is focused on the design and implementation of electronic hardware and software, it also includes a uuique mechanical design of the instlUment enclosure anangement. Pasteurization is the process applied to a beverage product (in this case beer) to obtain sterility and micro-biological stabilization [15]. In this process, heat is applied to a product in a container in order to killllllwanted bacteria and micro-organisms that impair the flavour and shelf-life of the product. A product that is pasteurized can be stored at room temperature in a warehouse with much longer shelf-life than nonnal products. In the brewety, pasteurization of packaged beer is accomplished by moving the beer containers on a wide' conveyor through a tlIllnel pasteurizer [2]. The container line moves slowly th.rough different compartments where water is sprayed over them. In each zone, nozzles spray water with specific zone temperatures over the beer containers. The beer containers move through the pasteUlizer on the conveyor, and are subjected to a sequential range of temperature zones which conelate with the specifications required by SAB. Pasteurizer specifications are supplied by the manufacturers of this equipment.
Thesis
Keywords: Brewing - Equipment and supplies - Data processing; Beer - Quality control - Data processing